Conducting Outcomes Research in a Clinical Practice Setting: The Effectiveness and Acceptability of Acceptance and Commitment Therapy (ACT) in a Partial Hospital Program. Issue 2 (March 2021) - Morgan, Theresa A.; Dalrymple, Kristy; D'Avanzato, Catherine; Zimage, Sarah; Balling, Caroline; Ward, Madeline; Zimmerman, Mark
Abstract: Multiple challenges exist integrating research into clinical practice, particularly in acute care settings where randomized controlled trials may be impractical or unethical. Partial or day hospitals are one such setting. As compared to outpatients and inpatients, relatively little research is conducted or reported in partial hospital program (PHP) patients, leaving providers in this setting without a solid empirical basis from which to draw. We report treatment outcomes and patient satisfaction from the first 750 patients enrolled in a clinical research PHP utilizing the acceptance and commitment therapy (ACT) treatment model. ACT is a well-established, transdiagnostic behavior therapy. However, to date no study has examined the use of ACT in acute day hospitals. We hypothesized that applying ACT with this patient group would result in significantly improved depression, anxiety, functioning, and quality of life from intake to discharge. We additionally expected that patients would report high satisfaction with ACT treatment groups. Patients ( n = 750 full sample, n = 518 completed treatment) completed daily measures of symptoms, functioning, and ACT processes at intake and discharge, and postgroup satisfaction surveys. Results showed significant improvements in symptoms and impairment. ACT process variables also increased over the course of treatment. Importantly, patient satisfaction was high for all groups. Thus, ACT provides an appropriate, flexible, effective, and satisfactory model for this patient group. A comparison of our findings using ACT to the limited research using other models in PHP settings is discussed, as well as challenges in the overall process of integrating research into routine clinical care. Highlights: Barriers do not prohibit practice-based research in acute psychiatric settings Acceptance and commitment therapy yields positive partial hospital outcomes Patient satisfaction is high for acceptance and commitment therapy groups More clinical research is needed in partial hospital and other intensive settings